Cuidados paliativos nos serviços de atenção domiciliar do Sistema Único de Saúde: revisão integrativa de literatura - Carla Regina Carvalho Silva Gonçalves; Eliane Dias Gontijo; Ana Claudia Garcia Mesquita (2023)
Palliative care is an approach that improves the quality of life for patients and their families who face problems associated with severe illnesses that threaten the continuation of life. This integrative review aimed to analyze the national scientific production on palliative care in home care and identify the strategies and challenges for its implementation in the home care service (Programa Melhor em Casa) within the Unified Health System (Sistema Único de Saúde). The search found 1,488 studies, of which 19 (1.3%) met the eligibility criteria, with nine (47.4%) being dissertations, eight (42.1%) articles, and two (21%) theses. 62% of the studies were conducted in the South/Southeast region. The studies were organized into five thematic categories: a) public policies in palliative care in home care, which highlight the absence of specific public policies on the subject, with resource allocation; b) the caregiver, describing how the caregiver enables home care while facing various challenges such as the feminization of care, overload, and a scenario of vulnerabilities and frailties in physical, social, psychological, and financial aspects, pointing to the absence of public policies supporting care; c) communication in palliative care, emphasizing the importance of communication as a crucial tool for enabling this care; d) professional training in palliative care, presenting the fragility of professional training and outlining guidelines to contribute to the development of a culture in palliative care; e) care management - technical and cultural aspects, which was subdivided into two subcategories. The first subcategory, Clinical management in palliative care: organizational aspects, highlighted the need to build patient- centered care models with humanistic and scientific pillars. The second subcategory, holistic approach to symptom control - total pain, discussed the importance of a multidimensional approach to the individual and their family. The review indicated the need to chart a path towards the implementation of palliative care in home care, involving various stakeholders such as the state, users, and workers, in overcoming challenges and building robust public policies so that palliative care can be offered as a human right. It emphasizes the need to develop intervention models with humanistic principles that value the different dimensions of comprehensive care based on technical and scientific issues and interprofessionality, considering that the demands of patients and families go beyond purely technical and procedural approaches, but are centered on the preservation of human dignity. There is an urgent need to shift from curing to caring, the true essence of palliative care.